2013
DOI: 10.1016/j.psyneuen.2013.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory mechanisms of cortisol effects on emotional learning and memory: Novel perspectives

Abstract: Summary It has long been known that cortisol affects learning and memory processes. Despite a wealth of research dedicated to cortisol effects on learning and memory, the strength or even directionality of the effects often vary. A number of the factors that alter cortisol’s effects on learning and memory are well-known. For instance, effects of cortisol can be modulated by emotional arousal and the memory phase under study. Despite great advances in understanding factors that explain variability in cortisol’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 56 publications
1
29
1
2
Order By: Relevance
“…A few studies have examined the relationship between pre-learning baseline cortisol levels and free recall in healthy young adults, and have either reported no significant relationship (e.g., Ackerman et al, 2013), or a significant association only under certain conditions, such as after intentional but not incidental encoding (Preuß, Schoofs, & Wolf, 2009), after a night of sleep but not after a no-sleep delay of equal length (Bennion, Steinmetz, Kensinger, & Payne, 2013), and when the materials are emotional rather than neutral (Preuß et al, 2009). Although in the two latter studies a positive association was observed between pre-learning cortisol levels and memory performance, negative relationships between baseline cortisol and memory performance have also been reported in healthy young adults (e.g., Van Honk et al, 2003). However, no previous study that we are aware of has examined the relationship between pre-learning cortisol levels and recognition memory or the processes of recollection and familiarity.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…A few studies have examined the relationship between pre-learning baseline cortisol levels and free recall in healthy young adults, and have either reported no significant relationship (e.g., Ackerman et al, 2013), or a significant association only under certain conditions, such as after intentional but not incidental encoding (Preuß, Schoofs, & Wolf, 2009), after a night of sleep but not after a no-sleep delay of equal length (Bennion, Steinmetz, Kensinger, & Payne, 2013), and when the materials are emotional rather than neutral (Preuß et al, 2009). Although in the two latter studies a positive association was observed between pre-learning cortisol levels and memory performance, negative relationships between baseline cortisol and memory performance have also been reported in healthy young adults (e.g., Van Honk et al, 2003). However, no previous study that we are aware of has examined the relationship between pre-learning cortisol levels and recognition memory or the processes of recollection and familiarity.…”
Section: Introductionmentioning
confidence: 84%
“…There is good evidence, primarily from animals but also from human studies, that glucocorticoids influence memory via actions on mineralocorticoid (MR) and glucocorticoid receptors (GR) in medial temporal lobe structures, and that the MR/GR binding ratio can determine how stress impacts memory. Both GRs and MRs are found in the hippocampus (and amygdala), but MRs are found in much lower densities in cortical regions (for a review, see van Ast et al, 2013). Thus, the effects of stress on different memory processes may be a function of the ratio of GR and MR receptors in the brain regions supporting those processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hay evidencia que señala que los eventos con contenido emocional se recuerdan en mayor medida que los neutros (Bradley et al, 1992;Cahill & McGaugh, 1995Christianson, 1992;van Ast et al, 2013). Dolcos, LaBar y Cabeza (2004) demostraron que el recuerdo de imágenes (tanto placenteras como displacenteras) con contenido emocional es mayor que el de las imágenes neutras.…”
unclassified